Assessment of Chronic Drug Abuse on some Biochemical and Hematological Parameters in Human: A Multivariate Analysis - Ali, Ruaa H.; Edan, Luma M.; Al-Rubai, Haider K.; Jaafar, Saba R.; Bedair, Nada H. (Iraqi Journal of Science, 2025)
Ongoing substance abuse poses substantial public health concerns, primarily due to its wide-ranging impact on physiological processes. This study investigates the biochemical and hematological alterations associated with long-term drug abuse and seeks to elucidate the broader physiological consequences for both clinical assessment and public health planning. In the present case-control study, 100 male participants were divided into 60 drug abusers and 40 non-abusers. Thyroid hormones, liver enzymes, kidney function tests, and hematological tests like CBC (complete blood count) were analyzed in blood samples. There were notable differences between the groups; drug abusers showed higher serum levels of T4, urea, ALP, alanine transaminase (ALT), white blood cells (WBC) and lymphocyte counts, and lower levels of hematocrit (HCT) and red blood cells (RBC). No significant difference was found between drug use duration or frequency and the aforementioned parameters. The findings emphasize the importance of regular monitoring of these measures in people with history of drug abuse. Also, the study highlighs the need for more research to determine the mechanisms underlying these changes and potential interventions.